2017
DOI: 10.1089/trgh.2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and Gender Nonconforming in Emergency Departments: A Qualitative Report of Patient Experiences

Abstract: Background: Individuals who have a transgender or gender nonconforming (TGGNC) experience belong to a marginalized segment of the U.S. population, and healthcare can be difficult for them to navigate. Although emergency departments (EDs) traditionally serve as healthcare “safety nets” for vulnerable populations, quantitative studies outside the United States have found that TGGNC-experienced persons tend to avoid EDs and/or have negative experiences. This qualitative study primarily describes the ED experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 19 publications
1
102
0
2
Order By: Relevance
“…Despite these limitations, our results mirror the social disparities seen in other studies and are consistent with the Minority Stress Model. 6,7,9,18,[28][29][30] Despite having higher levels of education compared to the general population, 13% of our sample reported being unemployed and 42% reported an annual income less than $24,000. These are comparable to the 2015 US Transgender Survey where 16% of respondents were unemployed and 55% reported annual incomes less than $24,000.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Despite these limitations, our results mirror the social disparities seen in other studies and are consistent with the Minority Stress Model. 6,7,9,18,[28][29][30] Despite having higher levels of education compared to the general population, 13% of our sample reported being unemployed and 42% reported an annual income less than $24,000. These are comparable to the 2015 US Transgender Survey where 16% of respondents were unemployed and 55% reported annual incomes less than $24,000.…”
Section: Discussionmentioning
confidence: 76%
“…This aligns with other studies that have found that increased support, provider knowledge about transgender issues, and access to transition-related care improve mental health. 7,30,32 Provider training may be one component of a multi-pronged strategy for improving the health of transgender patients. The Veterans Affairs conducted a multi-site provider training that demonstrated the feasibility of implementing training programs, increased provider self-confidence, and intent to treat more transgender patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training for all clinicians and patient-facing health professionals, including emergency departments and administration and clerical staff, are very much required, and professional societies need to place TGD health as a training priority [10,14,17]. Moreover, more investment in training programs nationally is very much needed, as well as the implementation of trans cultural awareness amongst various health professional degrees and accreditations.…”
Section: Discussionmentioning
confidence: 99%
“…Health policy, material deprivation, inequality, and stigma are implicated in poor health outcomes among emergency department (ED) patients . Researchers have emphasized the role of the social determinants of health, structural racism, gender discrimination, homophobia, and transphobia on the health of ED patients. These topics continue to gain interest and attention as their ties to medical education, clinical care, and population health are elucidated and emphasized.…”
mentioning
confidence: 99%